From dripline to dripline: Nuclear astrophysics in the laboratory. (August 2016) - Meisel, Zach
Abstract: For the better part of a century the field of nuclear astrophysics has aimed to answer fundamental questions about nature, such as the origin of the elements and the behavior of high-density, low-temperature matter. Sustained and concerted efforts in nuclear experiment have been key to achieving progress in these areas and will continue to be so. Here I will briefly review recent accomplishments and open questions in experimental nuclear astrophysics.